Immunohistochemistry of the chondroitin sulfate epitope in various normal human tissues of fresh cadavers - Keerewatcharaporn, Opat; Ongchai, Siriwan; Loawatnapong, Sikrai; Peerapapong, Lamaiporn; Pothacharoen, Peeraphan; Aungsuchawan, Sirinda (Biomedical Sciences and Clinical Medicine, 2016)
Objective The purpose of this study was to reveal the expression trend of the WF6 epitope in various normal human tissues. Methods Ten types of tissue samples from the brain, adipose, skeletal muscle, tendon, liver, cartilage, cardiac muscle, lung, nerve, and, skin were used in this study. They were obtained from fi ve fresh cadavers aged 20-70 years and stained with H and E for their general morphology. In addition, expression of the WF6 epitope was examined using immuno localization. Results The results demonstrated that WF6 epitope expression in the ten tissues can be categorized into three levels, with the highest being found in the brain, skeletal muscle, cartilage, cardiac muscle and skin tissues. A moderate level was found in the adipose, liver, lung and nerve tissues, and the lowest level was found in the tendon tissue. Conclusion The WF6 epitope was expressed at different levels in all of the various normal tissues. This refl ects the important role of this biomolecule for all cells, which may be benefi cial for further study in pathological tissues.